Malpractice lawsuits in orthopedic trauma surgery: a meta-analysis of the literature. Issue 3 (28th September 2022) - Thabet, Ahmed M.; Adams, Austin; Jeon, Soyoung; Pisquiy, John; Gelhert, Rick; DeCoster, Thomas A.; Abdelgawad, Amr
Abstract: Introduction: The objectives for this study were to identify whether diagnostic or procedural errors more commonly resulted in lawsuit, as well as to elucidate how specific variables affected mean indemnity. Methods: Systematic review of English-language articles in the PubMed and Google Scholar databases (through 2020) using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Meta-analysis was performed to estimate measures of proportions and differences in mean indemnity. Results: The estimated probability of lawsuits related to orthopedic trauma in overall studies was 23.3%. There were no significant rate differences between main causes of claims (diagnostic vs procedural errors) and areas of injury (upper vs lower). There was no significant difference of mean indemnity between the probabilities of trauma-related claims, diagnostic error, and procedural error. Conclusion: Non-trauma cases were more likely to result in lawsuit than trauma cases. Procedural errors accounted for most malpractice claims. The average indemnity increased according to the higher diagnostic errors, while the indemnity was lower with a relatively higher proportion of procedural errors. The most common cause of litigation varied between studies; however, among the most cited reasons were missed diagnosis/error in diagnosis, improper/substandard surgical performance, and, though not specifically studied in this analysis, errors of informed consent. Level of Evidence: Economic and Decision Analyses Level VI